2023
DOI: 10.1002/pc.27528
|View full text |Cite
|
Sign up to set email alerts
|

Formation and stability of the conducting cluster in the composite filaments based on polylactide and carbon nanofibers

Abstract: Composite threads based on polylactide (PLA) containing up to 20 wt% carbon nanofibers (CNF) were produced using melt technology. The formation of a percolation cluster was studied in composite filaments with various morphologies (non‐oriented, subjected to isothermal crystallization, and oriented by six times). By adding 20 wt% CNF, a specific resistance of 100 Ohm m was achieved in the PLA filament. With orientation stretching, the specific resistance was 107 Ohm m, regardless of the CNF concentration. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Even after 12 months of implantation, the conductive properties were maintained. Although, the strength of composite filaments decreased by 20% of the initial value, while pure PLA filaments retained 55% of their original strength 360 . Among all these, GO has been widely explored due to high solubility, good biocompatibility and low cost.…”
Section: Nano Particles (Nps)mentioning
confidence: 99%
“…Even after 12 months of implantation, the conductive properties were maintained. Although, the strength of composite filaments decreased by 20% of the initial value, while pure PLA filaments retained 55% of their original strength 360 . Among all these, GO has been widely explored due to high solubility, good biocompatibility and low cost.…”
Section: Nano Particles (Nps)mentioning
confidence: 99%
“…Its material properties are demonstrated in Table 3 [17,18]. Von Mises yield function was applied for both filler and matrix included in the model (8,9).…”
Section: Numerical Modelmentioning
confidence: 99%
“…Previous research has indicated that the introduction of organic additives to PLA complicates the process-structureproperty relationship within FDM manufacturing. Despite extensive research efforts exploring the effects of various parameters, such as raster angle, additive volume, and layer height, on the mechanical properties and geometric precision of PLA/biocomposite components, a comprehensive understanding of the threshold relationship remains elusive [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For CPC, the percolation threshold is the minimum amount of conductive filler needed to make the composite electrically conductive. 21 Common conductive fillers 22 used in CPC include metals, metal oxides, magnetic ferrites, and carbon-based materials, 23,24 etc. The conductivity of CPC is directly connected with the amount of conductive fillers present.…”
Section: Introductionmentioning
confidence: 99%